An Analysis of the Relationship Between Strategic Management and Firm Performance: A Case of Telecommunication Firms in Saudi Arabia - Mohammed A, Alzahrani Murshid (2011)
The advantages of studying the analysis of relationship between the strategic planning processes and firm performance cannot be overemphasized, especially in the clustering industrials or firms environments where it is mainly used as a measured for strategic planning processes’ selection. Achieving organizational effectiveness is an exclusive and continuing struggle for every organizations or firms in Saudi Arabia, while many efforts that involve a huge amount of money are invested towards to meet this crucial aim. However, there has not been a research about the analysis of the relationship between the strategic planning processes and firm’s performance in Saudi Arabia, which is seen as a way for organizations to meet their set target for the yearly activities. Therefore, this study is presented to analysis the relationship between planning process and firm performance of telecommunication firms in Saudi Arab for proper method’s selection which will be benefited for the firms. The use of proportionate stratified random sampling was adopted where questionnaires were distributed among executives of the selected firms. The total of 120 executives was chosen from 20 selected firms as sample of this study. Thus, this study has helps to define the factors that required a crucial attention in the planning process and exhibited approach needed to have effective and profitable organizational performance in Saudi Arabia market.